A cachaça nos dois lados do Atlântico: produção comércio e proibição - Ricardo, Raphael Martins [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In the brazilian colonial period, mainly between the years of 1640 and 1695, the cahaca's production and commercialization had suffered innumerable legislative measures by the Portuguese Crown in order to regulating these activities, to the point of being forbidden. This attitude was motivated by the constant claims of the portuguese producers of wine who pointed the drink as they direct competitor and responsible for the fall of the sales of their product. Moreover, it had masters of sugar mill's claims, which passed for difficulties generated by the competition of the sugar produced in the Antilles, that the Crown to take some measure against the manufacture of the drink, therefore was they direct competition in the commerce of the sugar cane and firewood (used in the stills/alambique). Amid these commercial and economic order conflicts, the Jesuit priests also were hostile to the cachaça's consumption, since they blamed it for the degeneration of the indians and slaves bodies and souls. All these tensions left the Crown in a delicate position, therefore cachaça was the main product in the African commerce of slaves and responsible for the reorganization of a regular commerce between Brazil and the African trade. In this sense, this project has as main objective to analyze the economics and politics impediments for which cachaça´s production passed during this period, trying to understand the complicated situation of the Crown, that depended of incomes proceeding from distinct sources, not being able, therefore, unconditionally ally itself to one of the sides. Reason of their vacillating attitude, sometimes forbidding the cachaca's production, sometimes authorizing and being rigid

No período colonial brasileiro, principalmente entre os anos de 1640 e 1695, a produção e comercialização da cachaça sofreram inúmeras medidas legislativas por parte da Coroa Portuguesa a fim de regular essas atividades, chegando ao ponto de serem proibidas. Essa atitude fora motivada pelas constantes reclamações dos produtores de vinhos portugueses que apontavam a bebida como sua concorrente direta e como responsável pela queda da venda de seu produto. Além disso, havia reivindicações por parte dos senhores de engenho, os quais passavam por dificuldades geradas pela concorrência do açúcar produzido nas Antilhas, para que a Coroa tomasse alguma medida contra a fabricação da bebida, pois esta era sua concorrente direta no comércio da cana e lenha (utilizada nos alambiques). Em meio a esses conflitos de ordem comercial e econômica, os padres jesuítas também se mostravam hostis ao consumo da cachaça, já que a culpavam pela degeneração do corpo e da alma dos indígenas e escravos. Todas essas tensões deixavam a Coroa em uma posição delicada, pois a cachaça era a principal mercadoria do comércio de escravos e responsável pela reestruturação de um comércio regular entre o Brasil e as praças africanas. Neste sentido, este projeto tem como objetivo principal analisar os entraves políticos e econômicos pelos quais a produção de cachaça passou durante este período, buscando entender a complicada situação da Coroa, que dependia das rendas provenientes de fontes distintas, não podendo, portanto, aliar-se incondicionalmente a um dos lados. Razão de sua atitude vacilante, ora proibindo o fabrico da cachaça, ora autorizando e ora fazendo vistas grossas
Keywords: Cachaça; Aguardente; Comércio; Brazil - History; Brasil - História - Período colonial, 1500-1822